Masyarakat Multikultural: Harmoni Antarumat Islam dan Kristen di Desa Prenggan, Sanggrahan, Grogol, Sukoharjo - Chusnaini, Nur; Purwanto, Danang (IAIN Madura, 2024)
In multicultural societies, religious differences can often lead to conflicts, making it essential to foster haarmony among religious communities. This study aims to examine how harmonious relationships between Muslims and Cristian are established, , developed, maintained, and internalized by the community in Prenggan village, Sanggrahan, Grogol, Sukoharjo. The research employs a qualitative method observation and in-depth interviews, while secondary data were obtained from literature sources such as book, journals, and articles. The findings indicate that maintaning harmony between Muslim and Cristians requires active contributions from individuals, families, religious leaders, the government, and the broader community. Social harmony is not a spontaneous condition but the result of a deliberate and continous social contruction process. This success has created a peaceful environment marked by mutual respect despite religious differences whitin the community